2022
DOI: 10.1108/jfra-08-2021-0215
|View full text |Cite
|
Sign up to set email alerts
|

The development of Islamic accounting education in the UAE and its challenges: an institutional perspective

Abstract: Purpose This paper aims to examine the development of Islamic accounting education and discuss the main challenges facing this specific type of accounting education in the United Arab Emirates (UAE). Design/methodology/approach The paper uses institutional theory to analyze the development of Islamic accounting education in the UAE. The collection of information in this study is based on secondary data available from published sources and websites. Findings This study identifies three types of institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Universities have attempted to mimic other prototypes in comparable circumstances in the field of higher education by using mimetic processes (Tiron-Tudor et al, 2022). In this relation, the tested result by Grassa, Khlif and Khelil (2022) found that mimetic pressures are supported while the adoption of Islamic accounting education-focused programmes in regional colleges by the UAE Government attributable to Islamic universities established in Malaysia, Indonesia, and Pakistan.…”
Section: Mimetic Pressure and Accounting Education Learning Contextmentioning
confidence: 99%
“…Universities have attempted to mimic other prototypes in comparable circumstances in the field of higher education by using mimetic processes (Tiron-Tudor et al, 2022). In this relation, the tested result by Grassa, Khlif and Khelil (2022) found that mimetic pressures are supported while the adoption of Islamic accounting education-focused programmes in regional colleges by the UAE Government attributable to Islamic universities established in Malaysia, Indonesia, and Pakistan.…”
Section: Mimetic Pressure and Accounting Education Learning Contextmentioning
confidence: 99%
“…These challenges emanate in different perspectives, which include less patronage of their products (Hidayat et al , 2020), an issue argued to be exacerbated by lack of awareness and knowledge of the IFIs’ activities (Umar and Kurawa, 2021). In a related development, there is also a growing concern about Islamic accounting education (Grassa, Khlif and Khelil, 2022), especially in the West-African countries where Islamic accounting education is not popular. In Nigeria, for instance, apart from Bayero University, Kano, which offers Islamic accounting-related courses through its International Institute of Islamic Banking and Finance, the authors could not find any among the north-western universities that offer Islamic accounting and finance courses, including the Al-Qalam University Katsina, which was to the best of the authors’ knowledge claimed as the first and only Islamic university in the north-west region.…”
Section: Introductionmentioning
confidence: 99%